2017
DOI: 10.1002/mus.26003
|View full text |Cite
|
Sign up to set email alerts
|

AANEM policy statement on electrodiagnosis for distal symmetric polyneuropathy

Abstract: Electrodiagnostic (EDX) studies are often very helpful in the diagnosis and management of patients who have or are suspected to have Distal Symmetric Polyneuropathy (DSP). However, EDX studies may not be appropriate in every situation. There are five common scenarios in which EDX studies are likely to be beneficial: (1) determining primary and alternative diagnoses; (2) determining severity, duration and prognosis of disease; (3) evaluating risk of associated problems; (4) determining the effect of medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Even though small fibre neuropathy is the most prevalent, unfortunately it is usually not recognized by routine electrophysiologic studies which are limited to the study of large nerves. [ 4 ] This can lead to excessive investigation, which can cause a strain on resources and finances. In this study, we intend to examine the slow velocity small fibres responsible for small fibre DSPN, by isolating them using collision technique principle in routine electrophysiologic studies, in patients with T2D which would help provide a novel tool to identify this common neuropathy in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Even though small fibre neuropathy is the most prevalent, unfortunately it is usually not recognized by routine electrophysiologic studies which are limited to the study of large nerves. [ 4 ] This can lead to excessive investigation, which can cause a strain on resources and finances. In this study, we intend to examine the slow velocity small fibres responsible for small fibre DSPN, by isolating them using collision technique principle in routine electrophysiologic studies, in patients with T2D which would help provide a novel tool to identify this common neuropathy in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Distal symmetric polyneuropathy (DSP) is one of the most common reasons for electrodiagnostic testing (EDX) referrals. [1][2][3] The value those results carry in the management of patients is controversial. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…unsuspected diagnoses for which effective disease-modifying therapy exists. 2 This policy statement specifically alludes to the importance of identifying chronic inflammatory demyelinating polyneuropathy (CIDP), a disabling and potentially treatable condition for which EDX is foundational to the diagnosis. 5 Other studies have shown that the prevalence of demyelinating neuropathies among patients referred for peripheral neuropathy is low.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Os estudos eletrodiagnósticos são sensíveis, específicos e apresentam medidas validadas para detecção de polineuropatia. 11 Avaliações eletrodiagnósticas incluem estudo de condução nervosa (ECN) e eletromiografia por agulha (EMG). No diagnóstico de polineuropatia, o ECN é a parte mais informativa da avaliação eletrodiagnóstica, pois fornece uma medida do estado funcional das fibras sensitivas e motoras.…”
Section: Introductionunclassified